"A Sickness which has Grown to Epidemic Proportions": American Indian Anti-and Decolonial thought During the Long 1960s. (2nd April 2020) - Cobb, Daniel M.; Barger, Sarah; Skopp, Lily
ABSTRACT: In the wake of World War Two and with the onset of decolonisation and the Cold War, the United States embarked on a mission to 'modernize' the economies and cultures of the so-called 'developing nations' of the 'Third World.' Throughout the 1950s and 1960s, Native rights advocates seized upon the language of modernisation, development, nation building, nationalism, anticolonialism, and decolonisation among them. They leveraged these concepts to advance a model for federal-Indian relations predicated on tribal sovereignty and self-determination. In so doing, they became active participants in a global process of confronting and reassessing United States domestic and foreign policy and, in time, the very history of European colonialism and settler colonialism upon which they rested. Exploring the ideas of Native intellectuals, including D'Arcy McNickle (Flathead), Robert K. Thomas (Cherokee), Dorothy Davids (Stockbridge-Munsee), Clyde Warrior (Ponca), and Hank Adams (Assinibione), demands a re-evaluation of the Red Power era, challenges the tacit assumption that anti- and delonial thought emerged sui generis during the 1970 s, and proposes a more expansive and inclusive vision of American Indian intellectual history.